The use of the video format as a teaching guide - Monedero-Morales, Carmen del Rocío; Navarro Ardoy, Luis; Castro-Higueras, Antonio (Tuning Academy, 2023)
This article presents a pilot experiment on subjects from three Social Sciences degrees at two public Andalusian universities. The aim is to analyze the teaching guides and their presentation to students as a means of communicating with them, primarily through the video format instead of the conventional written format. To this end, attractive, clear and relatable video teaching guides have been developed to present to students, aware of the success of short videos dominating digital social networks, especially among younger age groups. A knowledge test was given to 99 students on the subject contents, as well as a satisfaction test; the following information was processed through the SPSS program. The main conclusion is that students have a high degree of satisfaction and a better knowledge of the new video guide format than the conventional written model.
Keywords: Enseñanza - Innovaciones; Enseñanza - Equipos y material; Control group; Experimental group; Teaching guide; Video; Video guide